2007
DOI: 10.1177/112067210701700204
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Two Ocular Anesthetic Methods for Phacoemulsification: Topical Anesthesia and Viscoanesthesia (Visthesia™)

Abstract: The results from the visual analog pain scale were comparable between groups, showing that VisThesia provides similar pain relief to topical anesthesia. Specular microscopy performed at 30 days postoperatively showed a significantly greater loss of endothelial cells with the use of VisThesia, suggesting that the 1% lidocaine concentration used in VisThesia may be toxic to corneal endothelial cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 34 publications
1
21
0
Order By: Relevance
“…There are only two published clinical studies of viscoanaesthesia in cataract surgery patients (Poyales‐Galan & Pirazzoli 2005; Perone et al. 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are only two published clinical studies of viscoanaesthesia in cataract surgery patients (Poyales‐Galan & Pirazzoli 2005; Perone et al. 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Although viscoanaesthesia has been shown to provide similar pain relief to topical anaesthesia without intracameral lidocaine (Perone et al. 2007), we know of no studies comparing viscoanaesthesia with intracameral lidocaine.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these results, studies comparing mean ECL of patients who received viscous-dispersive OVDs versus those who received soft-shell technique (N ¼ 50 eyes, viscous-dispersive: 5%; N ¼ 50 eyes, soft-shell technique: 4.11%) and cohesive OVDs (N ¼ 123 eyes, viscous dispersive: 6.4%; N ¼ 116 eyes, cohesive: 8.8%) during phacoemulsification showed no significant difference in ECL between groups at 3 months follow-up [46,47]. One study concluded that ECL rates with the combination device were comparable to those reported for similar OVDs, whereas another study found significantly higher ECL with the combination device when compared with the use of a dispersive OVD at the beginning of surgery and a cohesive OVD prior to intraocular implantation [48,49]. Earlier studies reported varying results in ECL with this combination device.…”
Section: Ophthalmic Viscoelastic Devicesmentioning
confidence: 96%
“…The 0.4% ophthalmic solution was used for many years in the United States, but this compound is currently only available in combination with a vital dye, such as sodium fluorescein or disodium fluorexon, for use in applanation tonometry . Oxybuprocaine hydrochloride 0.4% ophthalmic solution is still routinely used in Europe for ophthalmic diagnostic and surgical procedures in human, and veterinary ophthalmology . To our knowledge, there have not been any published data documenting its effects on the corneal sensitivity in cats.…”
Section: Introductionmentioning
confidence: 99%